Pushing Toward Nicaea: A Conceptual Analysis of Biblical ‘Pressures’ and Nicene Trinitarianism - Butner, D. Glenn, Jr. (Reformed theological review, 2025)
The concept of ‘pressures’ has been widely used in recent work on the relationship between the Trinity and Scripture, particularly among scholars relying on the theological interpretation of Scripture. Despite that, the concept has often been conceptually underdeveloped. This article offers a taxonomy of different sorts of biblical pressures that lead to the doctrine of the Trinity, considering both viable meanings of the concept and more implausible variants.